e-Portfolio Innovation in Educational Professional Practice: A Study of Users’ Perceptions and Reflections - Saratapun, Narumon; Lertpongrujikorn, Nutwichida; Lertamornpong, Chanisvara (Journal of Inclusive and Innovative Education, 2023)
The purposes of this research were to reveal the perceptions and reflections of e-Portfolio innovation users in various dimensions during the educational professional practice of the Faculty of Education, Kasetsart University. Research population included 103 student teachers for the academic year 2021 in six major fields and 82 cooperating teachers and university supervisors of the student teachers, totaling 185 people. The research tools consisted of the questionnaire on the perception of suitability of the e-Portfolio (student version and teacher version) and semi-structured interview form on advantages, disadvantages, and suggested solutions for e-Portfolio improvement (student version and teacher version). The research tools were validated its quality by educational experts. Results revealed that e-Portfolio users perceived the suitability in many aspects especially the assessment criteria in educational professional practice,the ability to reflect the learning outcomes of students, its modernized information system which facilitates the recording of data as well as saving more time and money comparing to the production of paper-based portfolio. The major disadvantages of the e-Portfolio are the instability of the system. There was a problem on saving and editing data including the inaccurate appearance of the input data. Solution to this problem is that it is necessary to improve the stability of the system by experts and correction of its user-interface that suits the needs of all users.